METASTATIC MULTIPLE PRIMARY GASTROINTESTINAL MELANOMA: A CASE REPORT - D. N. Kostromitsky; A. Yu. Dobrodeev; S. G. Afanasyev; N. A. Li; N. V. Vasilyev; A. S. Podyablonsky (Сибирский онкологический журнал)
Primary gastrointestinal melanoma is a rare tumor with a frequency of 1 new case per 5–7 years. Over the past 100 years, there have been no more than 25 reported cases of primary melanoma of the stomach and colon. The rarity of the disease and nonspecific clinical features pose diagnostic challenges. The tumor is characterized by an aggressive growth and early metastasis. Case description. We present a rare clinical case of primary gastrointestinal melanoma with metastatic involvement of the adrenal glands, liver and retroperitoneal lymph nodes. Conclusion. To date, treatment standards for primary gastrointestinal melanoma have not been developed and are the subject of debate. However, palliative chemotherapy used for the treatment of primary skin melanoma may lead to disease stabilization in patients with gastrointestinal melanoma.